2010
DOI: 10.1111/j.1467-9876.2010.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Integrated Nested Laplace Approximations for the Evaluation of Veterinary Surveillance Data from Switzerland: A Case-Study

Abstract: Spatiotemporal disease mapping models have been used extensively to describe the pattern of surveillance data. They are usually formulated in a hierarchical Bayesian framework and posterior marginals are not available in closed form. Hence, the standard method for parameter estimation is Markov chain Monte Carlo algorithms. A new method for approximate Bayesian inference in latent Gaussian models using integrated nested Laplace approximations has recently been proposed as an alternative. This approach promises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…The cantonal veterinary authorities are responsible for the realization of federal veterinary legislation in each affiliated region. In Schrödle et al (2010) it was found that the number of reported cases within one region might depend on the canton it belongs to. Hence, cantons are considered as a second, coarser spatial grid.…”
Section: Inlamentioning
confidence: 99%
See 2 more Smart Citations
“…The cantonal veterinary authorities are responsible for the realization of federal veterinary legislation in each affiliated region. In Schrödle et al (2010) it was found that the number of reported cases within one region might depend on the canton it belongs to. Hence, cantons are considered as a second, coarser spatial grid.…”
Section: Inlamentioning
confidence: 99%
“…As discussed in Schrödle et al (2010), the number of reported cases per region might depend on the canton a region belongs to. For investigation of this fact, (2) is extended to a second, coarser spatial level: An i.i.d.…”
Section: Spatial Disease Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, INLA can be successfully used in a great variety of applications (e.g. Li et al, 2012;Riebler et al, 2012;Ruiz-Cárdenas et al, 2012;Martino et al, 2011;Roos and Held, 2011;Schrö-dle and Held, 2011a,b;Schrödle et al, 2011;Paul et al, 2010), also thanks to the availability of an R package named R-INLA (Martino and Rue, 2010). Furthermore, INLA can be combined with the Stochastic Partial Differential Equation (SPDE) approach proposed by Lindgren et al (2011) in order to implement spatial and spatio-temporal models for point-reference data.…”
Section: Introductionmentioning
confidence: 99%
“…Different extensions of the parametric and non-parametric models have been proposed by Schrödle and Held (2011b) and applied to counts of salmonellosis in cattle reported to the Swiss Federal Veterinary Office from 1991 to 2008. Schrödle et al (2011) propose another application for these models to analyse reported cases of bovine viral diarrhoea in Swiss cattle from 2003 to 2007. Blangiardo et al (2013) study the pattern of low birth weight for the 159 counties of US state of Georgia from 2000 to 2010, using the parametric formulation in Bernardinelli et al (1995) and the non-parametric formulation in Knorr-Held (2000) with INLA.…”
Section: Introductionmentioning
confidence: 99%